Analisis Penerapan Etika Bisnis Islam Dalam Penggunaan Timbangan Di Pasar Tradisional (Studi Pada Pasar Desa Rawa Jaya Kec. Tabir Selatan Kab. Merangin Jambi) - Pipit Putriani; Erwin Saputra Siregar; Saijun Saijun (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The era of development in economic activities that are increasingly rapid will cause business competition will also be high, business people often forget the existence of business ethics in Islam. The problem that will be caused is the deviation of bell selling transactions, especially in traditional markets, such as reducing the dose in the scale. The use of weighing systems in the market, as a result of the use of weighing systems that are not in accordance with Islamic business ethics, and there are still many traders who continue to use scales that are no longer suitable for use. This research is expected from the officials of Rawa Jaya Village to provide direct education related to the use of weighing systems in the market. Tbalance or dose is a measuring instrument commonly used by sellers / traders in the process of buying and selling transactions. Which can be calculated the scale traded in the form of ounces, kilograms, quintals, and others using scales Presentation of data and problems used, researchers use qualitative types of research. Based on the results of research conducted, the lack of knowledge for traders about understanding the ethics of Islamic business, especially in the use of weighing systems, so that it will be possible for these traders to cause losses for buyers. In the principles of Islamic business ethics strongly prioritize the values of the Qur'an. Because of this, some basic values in Islamic business ethics have principles derived from Islamic teachings.